Implementation of Individual Counseling for Inclusion-Based Teachers in Bulungan Regency, North Kalimantan - Siti Maliha; Siti Rahmi (Journal of Educational Development and Learning (JEDAL), 2025)
This study aims to describe the implementation of individual counseling given to teachers in inclusive schools in dealing with learning problems with students with special needs (ABK) in Bulungan Regency, North Kalimantan. This study uses a qualitative approach with a case study method. The subjects of the study were teachers and school counselors from three inclusion primary and secondary schools. The results of the study showed that individual counseling services were carried out with a flexible and collaborative approach, including teacher needs assessment, emotional mentoring, learning strategies, and mediation in classroom problems. Counselors play an active role as professional companions in supporting teachers to understand the characteristics of ABK and adjust inclusive learning methods. Despite obstacles such as the limited number of counselors and the lack of inclusive education training, the implementation of individual counseling has been proven to have a positive impact on teachers' readiness and ability to create friendly and adaptive learning for all students. In conclusion, individual counseling for teachers is an integral part of the support system in inclusive education in this region.